The factors shaping undergraduates' interests towards business / Abdul Rashid Abd Rahim and Aedrean Anthony - Abd Rahim, Abdul Rashid; Anthony, Aedrean (2016)
Involving in business requires students to be responsible to think towards their future. It giving them options not too depends on limited employments opportunity in firms (Amaran, 2015). Therefore, students will find this an alternative upon their graduation which helps in unemployment burdens. According to (Hashim, Zainol, & Shukory, 2008) early research shown significant relationship between newly establish business with student's performance in education and high chance of potential success in business to educated entrepreneur. As a result, student's performances affect the motivation factors in business setting. Becoming a successful entrepreneur require more than motivation and good academic preferences. It is a process of understanding and ability of a person to identify opportunity of a potential business. Moreover, ideas creation and innovation need to be promising in order products can be commercialised to customer. Therefore, all of the materials on what students have learned must be polish better in building strong foundation of a business. It was essential elements of this study to know readiness and what kind of setting student most prefer. Entrepreneurship has been seen as method to increase economic growth thus there are efforts done by countries to enhance this field by promoting entrepreneurship and encourage activities matter particularly among youth. (Hashim, Zainol, & Shukory, 2008). This study attempts to determine involvement and awareness of undergraduate student of Sabah in engaging to business activities. Hence, it rectify level of participation by undergraduate student that significance for future references. As argued by (Keat & Ahmad, 2012) students' attitude towards business ownership listed major obstacles toward the entrepreneurship process namely; lack of experience or lack of finance in which delay the path towards university students preferred future occupation choice. Therefore, any challenges endured by the undergraduate students must be known particularly in the scope of this study to explain necessary measures to overcome any dragging elements for the students. As a result, steps taken evaluate process into better projection of implementation.